Morphology of the male reproductive system and sperm in Tingidae (Hemiptera) - Rezende, Paulo Henrique (2024)
Tingidae is a family of Heteroptera that presents lace patterns on the pronotum and hemielytra, which gives them the popular name Lace Bugs. They are exclusively phytophagous, and many species are agricultural pests. Despite their importance, the group has been left underappreciated in recent years. This thesis focused on this family to address two main questions: How reliable is a sperm morphometrical approach as a taxonomical tool when analyzing 16 species at once? What can the ultrastructural aspects of their sperm tell us about the relationships among the Miroidea and Heteroptera? Morphological data on the reproductive system was also described. The morphometric analysis proved helpful in distinguishing species and was shown to be an excellent complementary taxonomic tool. Furthermore, through ultrastructural sperm analysis, the Tingidae resembled the general pattern found in Heteroptera, corroborating the group's synapomorphies. However, some peculiarities were observed regarding the formation of the centriole adjunct, which extends in the anteroposterior axis of the spermatids, flanking the nucleus. It also confirmed previous findings for their sister family, Miridae. Overall, these findings contribute to a better understanding of Tingidae's reproductive characteristics, expand the family's data, and help outline evolutionary scenarios for such characteristics and phylogenetic implications within the suborder Heteroptera. Keywords: Cimicomorpha. Miroidea. Spermatology. Spemiotaxonomy.